The roles of impulsivity, comorbid ADHD, and borderline personality disorder in patients with bulimia nervosa - Susanne Gilsbach; Julia Leuchtenberger; Beate Herpertz-Dahlmann; Ulrich Voderholzer; Kerstin Konrad; Georg von Polier; Jochen Seitz; Manfred Fichter (Eating and Weight Disorders)
Abstract Background Bulimia nervosa (BN) is a serious mental illness with impulsivity as a cardinal symptom. Impulsivity contributes to various other, often comorbid, mental disorders, such as attention deficit/hyperactivity disorder (ADHD) and borderline personality disorder (BPD). The aim of this study was to explore comorbidities of BN with ADHD and BPD as well as the contribution of impulsivity as an underlying trait linking these disorders. Methods Hundred and fifteen females with BN and 98 healthy matched controls (HC) (age range between 16 and 48 years) were assessed regarding adult and childhood-ADHD, personality disorders and impulsivity. Results Patients with BN were more impulsive (p < 0.001) and more often fulfilled criteria of childhood/adulthood ADHD (p < 0.001) than HC, and criteria of BPD than expected in the general population. Childhood-ADHD (p = 0.009) and BPD (p = 0.017) both were significant positive predictors for impulsivity scores found in patients with BN. Conclusion Comorbidity with ADHD and BPD often is prevalent in BN and associated with an increase in impulsivity, the latter being a relevant transdiagnostic trait. It might be beneficial to explore impulsivity as well as comorbidities in the clinical care of patients with BN. Level of evidence III Evidence obtained from well-designed cohort or case–control analytic studies.